Studies on the defect underlying the lysosomal storage of sialic acid in Salla disease. Lysosomal accumulation of sialic acid formed from N-acetyl-mannosamine or derived from low density lipoprotein in cultured mutant fibroblasts. - Renlund, M (1986)
Salla disease is a lysosomal storage disorder characterized by mental retardation and disturbed sialic acid metabolism. To study endogenous synthesis and breakdown of sialic acid, fibroblasts were incubated for 5 d in the presence and then in the absence of N-[3H]acetylmannosamine. Labeling of free sialic acid was 5-10 times higher in mutant than in normal cells. Radioactivity decreased in 4 d by 75% in normal but only by 30% in mutant fibroblasts. The labeling pattern was not normalized upon coculture of mutant and normal cells. To study the metabolism of extracellular sialic acid, low-density lipoprotein (LDL) was labeled in the sialic acid moiety (periodate-NaB3H4) or in the protein moiety (125I). Binding, internalization, lysosomal degradation, and exit of products of protein catabolism were similar in normal and mutant fibroblasts. Upon incubation with LDL labeled in the sialic acid moiety, mutant cells accumulated 2-3 times more free sialic acid radioactivity than normal fibroblasts, mostly in the lysosomal fraction. After a 24-h chase incubation, radioactivity in free sialic acid decreased by 70-80% in normal but only by 10-30% in mutant cells. In mutant fibroblasts, 40% of the radioactivity remained in lysosomes, whereas no labeled free sialic acid was detected in lysosomes from normal fibroblasts. We conclude that in Salla disease, fibroblast endogenous synthesis of sialic acid and lysosomal cleavage of exogenous glycoconjugates is normal, but free sialic acid cannot leave the lysosome. These findings suggest that the basic defect in Salla disease is deficient transport of free sialic acid through the lysosomal membrane.